ANALISIS MODULUS ELASTISITAS DAN ANGKA POISSON BAHAN DENGAN UJI TARIK - SOUISA, MATHEUS (PATTIMURA UNIVERSITY, 2011)
Observation of the stress and strain in materials steel, brass and anneal is done by testing to determine the tensile modulus of elasticity of the material. The results showed that the modulus of elasticity of the material brass is smaller than the brass alloy steel and steel materials, caused by the formation of the composition of the material is different. The relationship between stress and strain are used to gain slope value, and this value used to determine the modulus of elasticity of steel materials, brass and anneal. The analysis showed that the magnitude of the modulus of elasticity of brass material ï«brass=(20.10 ï‚± 1.60) x109 Pa, anneal materials ï«anneal=(68.10 ï‚± 2.20) x109 Pa, and steel materials ï«steel=(201, 00 ï‚± 5.30) x109 Pa. The results of tensile tests conducted on all three materials can be used to determine the comparative figures Poisson. The analysis showed the amount of comparative figures in steel material Poisson msteel=0.106 ï‚± 0.002, brass material mbrass=0.104 ï‚± 0.002 and anneal materials manneal=0.103 ï‚± 0.005. Figures Poisson appeal on steel materials is greater than the brass and anneal